2021
DOI: 10.1038/s41467-021-20986-y
|View full text |Cite
|
Sign up to set email alerts
|

LPA signaling acts as a cell-extrinsic mechanism to initiate cilia disassembly and promote neurogenesis

Abstract: Dynamic assembly and disassembly of primary cilia controls embryonic development and tissue homeostasis. Dysregulation of ciliogenesis causes human developmental diseases termed ciliopathies. Cell-intrinsic regulatory mechanisms of cilia disassembly have been well-studied. The extracellular cues controlling cilia disassembly remain elusive, however. Here, we show that lysophosphatidic acid (LPA), a multifunctional bioactive phospholipid, acts as a physiological extracellular factor to initiate cilia disassembl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 72 publications
(56 reference statements)
0
27
0
Order By: Relevance
“…The MT-dependent resorption is regulated by AuroraA kinase: It phosphorylates histone deacetylase HDAF6 and thereby triggers tubulin de-acetylation in the axoneme ( Pugacheva et al, 2007 ). Lysophosphatic acid (LPA), a phospholipid derivative, is involved in AuroraA-dependent primary cilium disassembly by activating the YAP/TAZ signaling pathway ( Hu et al, 2021 ). In addition, phosphorylation of AuroraA is catalyzed by a calmodulin/calcium-dependent protein kinase.…”
Section: Primary Cilium Disassembly: License For Mitosismentioning
confidence: 99%
See 1 more Smart Citation
“…The MT-dependent resorption is regulated by AuroraA kinase: It phosphorylates histone deacetylase HDAF6 and thereby triggers tubulin de-acetylation in the axoneme ( Pugacheva et al, 2007 ). Lysophosphatic acid (LPA), a phospholipid derivative, is involved in AuroraA-dependent primary cilium disassembly by activating the YAP/TAZ signaling pathway ( Hu et al, 2021 ). In addition, phosphorylation of AuroraA is catalyzed by a calmodulin/calcium-dependent protein kinase.…”
Section: Primary Cilium Disassembly: License For Mitosismentioning
confidence: 99%
“…In addition, phosphorylation of AuroraA is catalyzed by a calmodulin/calcium-dependent protein kinase. As a consequence, knockout embryos for the LPA receptor1 (LPAR1) show abnormally long primary cilia and reduced levels of both BPs and neurons ( Hu et al, 2021 ; Figure 2B ). A similar phenotype has been observed for mouse embryos mutant for either CenpJ/CPAP/Sas4, a MT-binding protein involved in centrosome maintenance and spindle orientation, or Kif2a, a kinesin motor protein ( Figure 2B ).…”
Section: Primary Cilium Disassembly: License For Mitosismentioning
confidence: 99%
“…Therefore, we suppose that the LPA/LPAR1-YAP axis may have a prospective impact on osteoimmune-mediated osseointegration, but its specific regulatory mechanism needs further clarification. Interestingly, the latest article revealed that LPA/LPAR1 pathway initiated cilia disassembly and promoted neurogenesis by activating the transcriptional coactivators YAP/transcriptional coactivator with a PDZ-binding motif (TAZ) signaling (Hu et al, 2021), which suggests the hypothesis that the role of the LPA/LPAR1-YAP pathway in neurogenesis could be generalized to dental implantation field by establishing osseoperception in bone-implant interface in order to compensate for the missing sensory functions of periodontal ligament. Therefore, osseoperception and osteoimmunology might share the same promising signaling target and synergistically promote bone healing and favorable osseointegration, which may be achieved by interdisciplinary work such as producing a pro-neurogenesis surface, which is also friendly to osteoimmunology by surface modification of implants.…”
Section: Nervous Systemmentioning
confidence: 99%
“…Therefore, studies on cilia length regulation might reveal essential determinants of energy homeostasis linked to obesity in individuals with ciliopathies, as well as other neuronal functions at the cellular level (23,24). Physiological modulation of ciliary length is achieved through multiple soluble factors, including leptin, lysophosphatidic acid, prostaglandin and lithium (25)(26)(27)(28)(29). However, there is no unified cilia length-determining pathway, as multiple signaling components that alter cilia length regardless of cell cycle period have been identified.…”
Section: Accepted Articlementioning
confidence: 99%